Future of Telecom and Thinkings on De-Telecom - Leping Wei (Dianxin kexue, 2013)
The paper started from the great changes of China telecom networks over the past 14 years and analyzed the past and present of telecom industry，and concluded the necessity of transformation. Then，the paper described the relationship between transformation and De-Telecom and presented main reasons why De-Telecom was necessary. In the fo11owing part，the paper introduced major trends of De-Telecom and difficulties. Then，the paper presented the continuous and enlarged gap between revenue and traffic and major ideas to dea1 with. Next，the paper elaborated major cha11enges and thinkings on IP and internet. In the fina1 part，the paper predicted 1ikely trends for telecom industry briefly.